2020
DOI: 10.1002/jat.3993
|View full text |Cite
|
Sign up to set email alerts
|

Structural binding perspectives of a major tobacco alkaloid, nicotine, and its metabolite cotinine with sex‐steroid nuclear receptors

Abstract: Globally, more than a billion people smoke tobacco making it one of the biggest public health problems and a leading risk factor for global deaths. Nicotine, the main alkaloid in tobacco, has been shown to be associated with fertility problems in men and women. The adverse effects of tobacco/nicotine on reproduction have been attributed to deleterious effects on gametes, steroidogenic imbalance, and competitive inhibition of steroid receptors. The present study reports the sex‐steroid receptor disrupting poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The native bound ligands were used as clue for the binding site and the residues around 10 Å of the native ligands were used as the binding site region for generating docking grid. Finally, the molecular docking of the compounds was performed using the rigid ligand docking option with default parameters and the docking poses and predicted results were generated, as detailed previously [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The native bound ligands were used as clue for the binding site and the residues around 10 Å of the native ligands were used as the binding site region for generating docking grid. Finally, the molecular docking of the compounds was performed using the rigid ligand docking option with default parameters and the docking poses and predicted results were generated, as detailed previously [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies involving nicotine and/or its metabolites on structural binding interactions against hormone carrier proteins such as SHBG, CBG, and TBG are not available to the best of our knowledge. However, recent structural binding and previous in vitro competitive binding studies have shown inhibitory interactions of nicotine and/or cotinine against steroid nuclear receptors [40,[50][51][52][53]. Nicotine is a powerful and addictive toxicant and has been reported to disturb the reproductive hormone levels including the SHBG levels in the circulation [54,55].…”
Section: Hormone Relationships Relevance and Conclusionmentioning
confidence: 99%
“…and progesterone, whereas TBG is responsible for the transport and availability of thyroid hormones (thyroxine, triiodothyronine). Computational methods have been increasingly used for the prediction of binding pose and molecular interactions of ligands with their target protein molecules, for designing novel inhibitors, and/or as an aid for designing experimental and clinical studies [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Nicotine is excreted as cotinine and 3′-hydroxy-cotinine in the urine, in body fluids such as blood and saliva, or the nails and hair. 6 Therefore, it can be used to measure recent exposure to nicotine, even low doses; a high concentration is usually observed 4 to 8 hours after exposure. 7 In addition, measurement of urinary cotinine (UC) is relatively inexpensive and easy and has high sensitivity and precision.…”
Section: Introductionmentioning
confidence: 99%